Molecular detection and characterization of Indian isolates of Pasteurella multocida serogroup ‘D’ - DUTTA, T K; SINGH, V P; KUMAR, A A (The Indian Journal of Animal Sciences, 2011)
Five Pasteurella multocida serogroup D isolated from pig (n=4, serotype D: 1) and sheep (n=1, serotype D: 3) were tested for molecular identification and characterization. All the isolates were detected by species specific PCR (PMPCR) and 460 bp products were obtained. RE analysis of the isolates using enzymes Hha I and Hpa II generated very clear and readable discriminatory banding profiles and 3 different RE profiles obtained out of 4 P. multocida isolates of serotype D: 1. Among the 2 enzymes used in this study, Hpa I had better discriminatory power than Hha I. Single primer based RAPD-PCR assay generated readable and distinct banding patterns between serotypes, but failed to differentiate 4 isolates of P. multocida serotype D: 1. Molecular detection using species specific PCR and characterization by molecular techniques like REA and RAPD-PCR could enable typing of P. multocida strains as a complement of classical capsular and somatic typing in preliminary characterization. Â